Child Abduction Cases in the European Court Of Human Rights – Changing Views on the Child’s Best Interests - Torunn E Kvisberg (Oslo Law Review, 2019)
Case law from the European Court of Human Rights has been important for the interpretation and application of the Hague Convention on International Child Abduction. The decisions both give authority to and complement the Hague Convention. Two landmark cases are the Grand Chamber judgments in Neulinger and Shuruk v Switzerland from 2010 and X v Latvia from 2013. The article analyses these two judgments, with a main focus on the Court’s application of the principle of the best interests of the child and the procedural requirements for return cases. The article also focuses on the relationship between child abduction cases and public child care cases. In case law after 2013, the Court applies the X principles in child abduction cases, while the requirements of Neulinger are still applied in public child care cases.